A bibliometric analysis of the relationship between traumatic brain injury and Alzheimer’s disease (1993-2023) - Hu, Ji-Hua; Zhang, Xin; Yang, Hong-Mei; Xu, Ya-Ling; Zhang, Ming; Niu, Xuan (Frontiers in Aging Neuroscience, 2024)
Background: Traumatic brain injury (TBI) increases the risk of developing Alzheimer's disease (AD), and a growing number of studies support a potential link between the two disorders. Therefore, the objective of this study is to systematically map the knowledge structure surrounding this topic over the past and to summarize the current state of research and hot frontiers in the field.Methods: Data were retrieved from the Web of Science Core Collection (WOSCC) starting from the beginning until December 31, 2023, focusing on articles and reviews in English. Bibliometric tools including Bibliometrix R, VOSviewer, and Microsoft Excel were utilized for data analysis. The analysis included citations, authors, institutions, countries, journals, author keywords, and references.Results: A total of 1,515 publications were identified, comprising 872 articles (57.56%) and 643 reviews (42.44%). The annual number of publications increased steadily, especially after 2013, with an R² value of 0.978 indicating a strong upward trend. The USA was the leading country in terms of publications (734 articles), followed by China (162) and the United Kingdom (77), while Boston University being the most productive institution. Collaborative networks show strong collaborative author links between the USA and the United Kingdom, as well as China. The analysis also showed that the Journal of Alzheimer's Disease was the most productive journal, while the article authored by McKee AC et al. in 2013 achieved the highest local citations value. The top three author keywords, in terms of occurrences, were "Alzheimer's disease," "traumatic brain injury," and "neurodegeneration". Thematic mapping showed a consolidation of research themes over time, decreasing from 11 main themes to 8. Emerging themes such as "obesity" and "diffusion tensor imaging" indicate new directions in the field.The research on AD after TBI has attracted a great deal of interest from scientists. Notably, the USA is at the forefront of research in this field. There is a need for further collaborative research between countries. Overall, this study provides a comprehensive overview of developments in TBI and AD research, highlighting key contributors, emerging topics, and potential areas for future investigation.